Global patterns and climate drivers of water‐use efficiency in terrestrial ecosystems deduced from satellite‐based datasets and carbon cycle models. Issue 3 (23rd December 2015) - Sun, Yan; Piao, Shilong; Huang, Mengtian; Ciais, Philippe; Zeng, Zhenzhong; Cheng, Lei; Li, Xiran; Zhang, Xinping; Mao, Jiafu; Peng, Shushi; Poulter, Benjamin; Shi, Xiaoying; et al.
Abstract: Aim: To investigate how ecosystem water‐use efficiency (WUE) varies spatially under different climate conditions, and how spatial variations in WUE differ from those of transpiration‐based water‐use efficiency (WUEt ) and transpiration‐based inherent water‐use efficiency (IWUEt ). Location: Global terrestrial ecosystems. Methods: We investigated spatial patterns of WUE using two datasets of gross primary productivity (GPP) and evapotranspiration (ET) and four biosphere model estimates of GPP and ET. Spatial relationships between WUE and climate variables were further explored through regression analyses. Results: Global WUE estimated by two satellite‐based datasets is 1.9 ± 0.1 and 1.8 ± 0.6 g C m −2 mm −1 lower than the simulations from four process‐based models (2.0 ± 0.3 g C m −2 mm −1 ) but comparable within the uncertainty of both approaches. In both satellite‐based datasets and process models, precipitation is more strongly associated with spatial gradients of WUE for temperate and tropical regions, but temperature dominates north of 50° N. WUE also increases with increasing solar radiation at high latitudes. The values of WUE from datasets and process‐based models are systematically higher in wet regions (with higher GPP) than in dry regions. WUEt shows a lower precipitation sensitivity than WUE, which is contrary to leaf‐ and plant‐level observations. IWUEt, the product of WUEt and water vapour deficit, is found to be rather conservative with spatially increasing precipitation, in agreement with leaf‐ and plant‐level measurements. Main conclusions: WUE, WUEt and IWUEt produce different spatial relationships with climate variables. In dry ecosystems, water losses from evaporation from bare soil, uncorrelated with productivity, tend to make WUE lower than in wetter regions. Yet canopy conductance is intrinsically efficient in those ecosystems and maintains a higher IWUEt . This suggests that the responses of each component flux of evapotranspiration should be analysed separately when investigating regional gradients in WUE, its temporal variability and its trends.